Spontaneous Hemoperitoneum due to Rupture of Uterine Varicose Veins during Labor Successfully Treated by Percutaneous Embolization - Rebeca Díaz-Murillo; Pablo Tobías-González; Sara López-Magallón; Fernando Magdaleno-Dans; José L. Bartha (Hindawi Limited, 2014)
Hemoperitoneum during pregnancy is a rare but potentially lethal clinical condition. Improvements in antenatal and intrapartum care, especially in surgical and anesthetic techniques, have reduced maternal mortality; perinatal mortality remains very high (31%). Treatment is based on the systemic correction of hypovolemia and immediate surgery via laparotomy or laparoscopy in cases in the first trimester of pregnancy for hemostatic purposes. Sometimes, hysterectomy is needed. A 35-year-old Asiatic primigravid woman at 37 weeks' gestation with otherwise uneventful pregnancy came to the hospital referring abrupt-onset lumbar and abdominal pain. A bleeding uterine superficial varicocele of about 7 cm was found on the left uterine horn during Caesarean section. Interventional radiologic embolization of both uterine arteries was successfully performed. Posterior evolution of the patient was favorable. Percutaneous vascular embolization of the uterine arteries is an effective alternative treatment for many obstetrical and gynecological causes of bleeding. The main advantage of this technique is the low rate of serious complications and the preservation of reproductive function. To our knowledge, this is the first case of spontaneous intrapartum hemoperitoneum treated with this technique. An early diagnosis and a rapid indication of this therapeutic option are essential. Hemodynamic stability is needed to decide this conservative management.